Structural Change and Inequality in Africa - Hanan Morsy; Abebe Shimeles; Tiguene Nabassaga (Institute of Labor Economics (IZA), 2021)
This paper examines how inequality could be tackled through structural transformation using unit record data from the Demographic and Health Surveys (DHS) for Africa. Results suggest inequality between countries tends to be higher when the share of labor employed or value-added in the agriculture sector is higher, while no effect is seen for industry and services sectors' contributions to employment or value-added of the gross domestic product (GDP). On the other hand, within-country inequality tends to be strongly affected by structural change. A one standard deviation growth in the movement of labor from low- to high-productivity sectors could decrease overall inequality by 0.5 percent and inequality of opportunity by 1.1 percent. Results from other data sources strongly support these findings suggesting that rapid structural transformation could lead to sustained reduction in inequality in Africa. Other factors correlated strongly with inequality reduction include human capital which tend to have large and significant income or asset equalizing effect in Africa, particularly at higher level of education. Growth in urbanization and high initial per capita GDP tend to worsen inequality, while initial inequality tended to stem the rise in inequality.
Keywords: D30; D31; J2; 330; structural transformation; inequality; labor productivity growth